My teacher is an alien - Coville, Bruce (Aladdin, 2014)
Uneasy about her new substitute teacher, Susan Simmons' suspicions about Mr. Smith are confirmed when she discovers he is an alien determined to bring some sixth-grade specimens back to his planet.